A new sensitive UPLC-MS/MS method for the determination of cucurbitacin B in rat plasma: application to an absolute bioavailability study. Issue 54 (5th September 2018) - Xiao, Ya; Zhao, Qiang; Wu, Qian; Chang, Jinhua; Xue, Hefei; Liu, Cuizhe; Liu, Xigang
Abstract : A method was developed for the determination of CuB in plasma using UPLC-MS/MS with estrone as an internal standard, and the pharmacokinetics and absolute bioavailability of CuB in rats were examined. Abstract : Cucurbitacin B (CuB) is a highly oxygenated tetracyclic triterpene, and a Biopharmaceutics Classification System (BCS) class IV drug used for the treatment of persistent hepatitis, chronic hepatitis, and primary liver cancer. Nevertheless, CuB has low solubility and low permeability, and is present at low concentrations in the human body. The aim of this study was to develop a method for the determination of CuB in plasma using ultra-performance liquid chromatography-mass spectrometry (UPLC-MS/MS) with estrone as an internal standard (IS), as well as to examine the pharmacokinetics and absolute bioavailability of CuB in rats. Plasma samples were processed by liquid–liquid extraction with ethyl acetate. Separation was achieved on a BEH C18 column (2.1 × 50 mm, 1.7 μm) at 35 °C using an isocratic mobile phase system with 0.1% formic acid–acetonitrile (50 : 50, v/v) at a flow rate of 0.3 mL min −1 . The detection was performed using a multiple reaction monitoring mode via a positive electrospray ionization interface. The calibration curves showed good linearity ( r = 0.9998) within the tested concentration ranges. The lower limit of quantification for plasma was 0.05 ng mL −1 ; the matrix effect of CuB and IS was 94.19–99.42% and 100.83%, respectively. The mean extraction recoveries from plasma were 85.34–90.53%. The intra-day and inter-day accuracies and precision deviations were within ±15%, which was in line with the allowable range of accuracy. In addition, the stability of the method was also verified. The absolute bioavailability of orally administered CuB in rats was 1.37%. To sum up, the presented method was determined to be suitable for the quantitation of CuB in rat plasma. Also, the absolute bioavailability observed in the present study suggested that it was necessary to change the dosage form to improve bioavailability, or to improve this by other means.